Epidemiological profile of women with endometriosis: a study in a tertiary care hospital in Bangladesh - Farhad, Sabrin; Roknuzzman, M.; Akhtar, Afroza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometriosis is a chronic and often painful condition characterized by the growth of tissue similar to the endometrium (the lining inside the uterus) outside the uterus. It primarily affects women of reproductive age and is a leading cause of pelvic pain and infertility. This study aimed to assess the epidemiological profile of women with endometriosis. Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynecology, Uttara Adhunik Medical College Hospital, Dhaka, Bangladesh from January 2022 to December 2022. As the study subjects, a total of 113 women with a confirmed surgical diagnosis of endometriosis enrolled in this study purposively. A purposive sampling technique was used in sample selection. Data were analyzed by MS Office tools. Results: The mean age of respondents was 32.1±5.2 years, 69% were housewives and 58% were married. Main complaints included cyclic pelvic pain (42.5%), acyclic pelvic pain (23.9%), heavy menstrual bleeding (14.2%), amenorrhea (4.4%) and palpable mass (6.2%). Premenstrual syndrome was observed in 72% of cases and 46% of participants were infertile. Investigations revealed 82.3% had ovarian cysts, 47.8% experienced dysmenorrhea and 31.9% suffered from primary infertility. Deeply infiltrating endometriosis was prevalent in 60.2%, 57.5% were in Stage-III/IV and 42.5% were in Stage-I/II. Conclusions: Endometriosis is most prevalent among younger married housewives. Main complaints include cyclic/acyclic pelvic pain, heavy menstrual bleeding, amenorrhea and palpable mass. Premenstrual syndrome and ovarian cysts are very common, while deeply infiltrating endometriosis being the most prevalent among endometriosis patients.